Early life stress modulates amygdala‐prefrontal functional connectivity: Implications for oxytocin effects. Issue 10 (26th May 2014) - Fan, Yan; Herrera‐Melendez, Ana Lucia; Pestke, Karin; Feeser, Melanie; Aust, Sabine; Otte, Christian; Pruessner, Jens C.; Böker, Heinz; Bajbouj, Malek; Grimm, Simone
Abstract Recent evidence suggests that early life stress (ELS) changes stress reactivity via reduced resting state functional connectivity (rs‐FC) between amygdala and the prefrontal cortex. Oxytocin (OXT) modulates amygdala connectivity and attenuates responses to psychosocial stress, but its effect appears to be moderated by ELS. Here we first investigate the effect of ELS on amygdala‐prefrontal rs‐FC, and examine whether ELS‐associated changes of rs‐FC in this neural circuit predict its response to psychosocial stress. Secondly, we explore the joint effect of OXT and ELS on the amygdala‐prefrontal circuit. Eighteen healthy young males participated in a resting‐state fMRI study of OXT effects using a double‐blind, randomized, placebo‐controlled, within‐subject crossover design. We measured the rs‐FC to bilateral amygdalae and subsequently assessed changes of state anxiety and prefrontal responses to psychosocial stress. Multiple linear regressions showed that ELS, specifically emotional abuse, predicted reduced rs‐FC between the right amygdala and pregenual anterior cingulate cortex (pgACC), which in turn predicted elevated state anxiety after psychosocial stress. In subjects with lower ELS scores, stronger pgACC‐amygdala rs‐FC predicted stronger pgACC deactivation during the psychosocial stress task, and this rest‐task interaction was attenuated by OXT. In subjects with higher ELS scores however, the rest‐task interaction was altered and OXT showed no significant effect. These findings highlight that ELS reduces pgACC‐amygdala rs‐FC and alters how rs‐FC of this circuit predicts its stress responsiveness. Such changes in pgACC‐amygdala functional dynamics may underlie the altered sensitivity to the effects of OXT after ELS. Hum Brain Mapp 35:5328–5339, 2014. © 2014 Wiley Periodicals, Inc.